Legume additions to the flora of China - Jiang, Kai-Wen; Tian, Bin; Pan, Bo (Phytotaxa, 2022)
Six legume taxa are added to the flora of China. Among them, two native taxa, Pueraria bella and Teyleria barbata, and one naturalized species, Desmodium uncinatum, are reported as newly recorded species, while Flemingia vestita is rediscovered and Flemingia yunnanensis is reinstated based on morphological evidence. Mucuna pruriens var. hirsuta is also newly recorded to China, and M. incurvata is considered as a new synonym of it. Comprehensive descriptions, photographs, conservation status assessments, and some taxonomic notes on these taxa, as well as updated keys to the taxa of Desmodium, Flemingia, Pueraria, and Mucuna subg. Stizolobium distributed in China are also given.